Vasoreactivity and inhaled treprostinil response in interstitial lung disease pulmonary hypertension - Eileen M. Harder; Farbod N. Rahaghi; Jane A. Leopold; David M. Systrom; George R. Washko; Aaron B. Waxman (ERJ Open Research)
Introduction Despite shared features with pulmonary arterial hypertension, acute vasoreactivity in pulmonary hypertension with interstitial lung disease (PH-ILD) is not well characterised, including its potential ability to predict therapeutic outcomes. We sought to determine whether acute vasoreactivity in PH-ILD to oxygen (O2) and inhaled nitric oxide (iNO) predicts inhaled treprostinil (iTre) outcomes. Materials and methods In this retrospective cohort analysis, we identified treatment-naive PH-ILD patients with vasoreactivity testing using O2 and O2+iNO. 6-month iTre outcome was assessed. “iTre improvement” required fulfilment of criteria on objective assessment without clinical worsening. “iTre failure” was defined by lack of objective improvement or a clinical worsening event. Results Among 75 PH-ILD patients, mean pulmonary arterial pressure (mPAP) decreased by −3 mmHg (−12.6%) and pulmonary vascular resistance (PVR) by −1.3 WU (−23.7%) with O2+iNO. With O2+iNO, mPAP decreased ≥10 mmHg to <40 mmHg in four patients (5.3%) and 23 (30.7%) had ≥20% reduction in mPAP and PVR. Among 33 iTre-treated patients, there were 13 improvements and 20 failures. The microvascular response, measured by distensibility, to O2 alone versus O2+iNO correlated with 6-month iTre outcome. Patients with 6-month iTre improvement had large relative distensibility increases with O2+iNO (versus failure, 76.0% versus 15.3%, p=0.004). Conversely, iTre failure was associated with increased distensibility with O2 alone (versus improvement, 26.8% versus −3.9%, p=0.045). Conclusions In PH-ILD, the microvascular response to O2 versus O2+iNO testing was associated with 6-month iTre outcome, likely reflecting the differential contributions of hypoxic vasoconstriction and remodelling. Acute vasoreactivity may inform therapeutic decision-making in PH-ILD.